The Soybean Sugar Transporter GmSWEET15 Mediates Sucrose Export from Endosperm to Early Embryo. Issue 4 (20th June 2019) - Wang, Shoudong; Yokosho, Kengo; Guo, Runze; Whelan, James; Ruan, Yong-Ling; Ma, Jian Feng; Shou, Huixia
Abstract : The sugar transporter GmSWEET15 is essential for soybean embryo development and endosperm breakdown as it mediates sucrose transport from the endosperm to the embryo. Abstract: Soybean ( Glycine max ) seed is primarily composed of a mature embryo that provides a major source of protein and oil for humans and other animals. Early in development, the tiny embryos grow rapidly and acquire large quantities of sugars from the liquid endosperm of developing seeds. An insufficient supply of nutrients from the endosperm to the embryo results in severe seed abortion and yield reduction. Hence, an understanding of the molecular basis and regulation of assimilate partitioning involved in early embryo development is important for improving soybean seed yield and quality. Here, we used expression profiling analysis to show that two paralogous sugar transporter genes from the SWEET (Sugars Will Eventually be Exported Transporter) family, GmSWEET15a and GmSWEET15b, were highly expressed in developing soybean seeds. In situ hybridization and quantitative real-time PCR showed that both genes were mainly expressed in the endosperm at the cotyledon stage. GmSWEET15b showed both efflux and influx activities for sucrose in Xenopus oocytes. In Arabidopsis ( Arabidopsis thaliana ), knockout of three AtSWEET alleles is required to see a defective, but not lethal, embryo phenotype, whereas knockout of both GmSWEET15 genes in soybean caused retarded embryo development and endosperm persistence, resulting in severe seed abortion. In addition, the embryo sugar content of the soybean knockout mutants was greatly reduced. These results demonstrate that the plasma membrane sugar transporter, GmSWEET15, is essential for embryo development in soybean by mediating Suc export from the endosperm to the embryo early in seed development.